Analysis of the Evolution of Trade in the Danube Region Countries - Hagiu, Alina; Bâldan, Cristina; Bărbulescu, Marinela (Journal of Danubian Studies and Research, 2024)
This analysis examines the recent evolution of trade in the Danube region over the period 2018-2023. The study explores key trade indicators including total trade volume, imports, exports, trade balance, major trading partners, and principal commodities. The region faced significant challenges and opportunities during this period, influenced by global factors such as the COVID-19 pandemic, shifts in global trade policies, geopolitical tensions, and advancements in green technologies. Findings reveal resilient economic responses, adaptation strategies to global disruptions, and varying levels of integration into global supply chains. Countries like Germany and Austria leveraged their industrial prowess and diversified exports to maintain robust trade performances. Central European countries benefited from foreign direct investments in manufacturing and green technologies, enhancing export capacities. Moreover, regional integration efforts within the European Union and strategic partnerships with neighboring countries played pivotal roles in sustaining trade flows. Challenges such as geopolitical instability and regional conflicts impacted trade dynamics in countries like Ukraine and Moldova, necessitating adaptive economic strategies. Looking forward, the region’s ability to innovate, diversify economies, and embrace sustainable practices will be crucial for navigating future global uncertainties and sustaining economic growth. This analysis provides insights into how each country in the Danube region navigated through economic challenges and capitalized on opportunities to strengthen their positions in the global trade landscape.